Optical and structural investigation of Cu2ZnSnS4 based solar cells. Issue 11 (1st August 2016) - Teixeira, Jennifer P.; Salomé, Pedro M. P.; Sousa, Marta G.; Fernandes, Paulo A.; Sadewasser, Sascha; da Cunha, António F.; Leitão, Joaquim P.
Abstract: The structural and optical properties of two solar cells in which the Cu 2 ZnSnS 4 absorber layer was sulphurized by two different methods (S flux and graphite box), were studied. The grain sizes are dependent on the sulphurization method, the larger ones being obtained for the sulphurization in a S flux. The optical properties were investigated by photoluminescence (PL). A broad and asymmetric band was observed for the sample with the larger grains, whereas for the other one a very broad emission was obtained, mostly influenced by the CdS buffer layer. The dependence on the excitation power revealed the influence of fluctuating potentials created by strong doping and high compensation of the absorber layer. Radiative recombination channels are quite different from the ones typical of semiconductor materials with flat bands. A relationship between the PL intensity from the absorber layer measured at low temperatures, and the final PV performance is established. Thus, we propose that PL can be used as an evaluation experimental technique in order to decide if a certain absorber should be processed into a full solar cell or not.